(untitled) (Baghdad Science Journal, 2019)
Out of 150 clinical samples, 50 isolates of Klebsiella pneumoniae were identified according to morphological and biochemical properties. These isolates were collected from different clinical samples, including 15 (30%) urine, 12 (24%) blood, 9 (18%) sputum, 9 (18%) wound, and 5 (10%) burn. The minimum inhibitory concentrations (MICs) assay revealed that 25 (50%) of isolates were resistant to gentamicin (≥16µg/ml), 22 (44%) of isolates were resistant to amikacin (≥64 µg/ml), 21 (42%) of isolates were resistant to ertapenem (≥8 µg/ml), 18 (36%) of isolates were resistant to imipenem (4- ≥16µg/ml), 43 (86%) of isolates were resistant to ceftriaxone (4- ≥64 µg/ml), 42 (84%) of isolates were resistant to ceftazidime (16-64 µg/ml), and 40 (80%) of isolates were resistant to cefepime (4- ≥16µg/ml). Co-Resistance for both β-lactams and aminoglycosides were detected among 25 (50%) of K. pneumoniae isolates. The extended spectrum beta-lactamases (ESBLs) were detected among 25 (50%) of K. pneumoniae isolates. Screening of 16S rRNA methylases encoding genes revealed that armA was found in 5 (10%) of K. pneumoniae isolates, whereas rmtB was not found among K. pneumoniae isolates. DNA sequencing of armA revealed that the presence of missense mutations in which affected in the translation of protein by substitutions of amino acids, leading to increase the resistance values of MICs for gentamicin and amikacin. These variants were registered in NCBI at the accession number LC373258. The phylogenetic tree of armA variants showed a slight deviation of these variants from K. pneumoniae species.